Examination of patient characteristics and hydroxychloroquine use based on the US Food and Drug Administration's recommendation: a cross-sectional analysis in New York. Issue 2 (8th February 2021) - Kim, Eun Ji; Coppa, Kevin; Hirsch, Jamie S; Abrahams, Sara; Johnson, Jennifer; Lesser, Martin; Davidson, Karina W; Conigliaro, Joseph
Abstract : Objective: To describe the pattern of hydroxychloroquine use and examine the association between hydroxychloroquine use and clinical outcomes arising from changes in the US Food and Drug Administration (FDA)'s recommendation during the coronavirus disease 2019 (COVID-19) pandemic. Design: A retrospective cross-sectional analysis. Setting and participants: We included hospitalised adult patients at Northwell Health hospitals with confirmed COVID-19 infections between 1 March 2020 and 11 May 2020. We categorised changes in the FDA's recommendation as pre-FDA approval (1 March 2020–27 March 2020), FDA approval (28 March 2020–23 April 2020), and FDA warning (24 April 2020–11 May 2020). The hydroxychloroquine-treated group received at least one dose within 48 hours of hospital admission. Primary outcome: A composite of intubation and inpatient death. Results: The percentages of patients who were treated with hydroxychloroquine were 192/2202 (8.7%) pre-FDA approval, 2902/6741 (43.0%) FDA approval, and 176/1066 (16.5%) FDA warning period (p<0.001). Using propensity score matching, there was a higher rate of the composite outcome among patients treated with hydroxychloroquine (49/192, 25.5%) compared with no hydroxychloroquine (66/384, 17.2%) in the pre-FDA approval period (p=0.03) but not in the FDA approval period (25.5% vs 22.6%, p=0.08) or the FDA warning (21.0% vs 15.1%, p=0.11) periods. Coincidently, there was an increase in number of patients with COVID-19 and disease severity during the FDA approval period (24.1% during FDA approval vs 21.4% during pre-FDA approval period had the composite outcome). Hydroxychloroquine use was associated with increased odds of the composite outcome during the pre-FDA approval period (OR=1.65 (95% CI 1.09 to 2.51)) but not during the FDA approval (OR=1.17 (95% CI 0.99 to 1.39)) and FDA warning (OR=1.50 (95% CI 0.94 to 2.39)) periods. Conclusions: Hydroxychloroquine use was associated with adverse clinical outcomes only during the pre-FDA approval period but not during the FDA approval and warning periods, even after adjusting for concurrent changes in the percentage of patients with COVID-19 treated with hydroxychloroquine and the number (and disease severity) of hospitalised patients with COVID-19 infections.